2016
DOI: 10.1007/s11010-016-2668-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of bovine sperm acrosomal proteins that interact with a 32-kDa acrosomal matrix protein

Abstract: Mammalian fertilization is accomplished by the interaction between sperm and egg. Previous studies from this laboratory have identified a stable acrosomal matrix assembly from the bovine sperm acrosome termed the outer acrosomal membrane-matrix complex (OMC). This stable matrix assembly exhibits precise binding activity for acrosin and N-acetylglucosaminidase. A highly purified OMC fraction is comprised of three major (54, 50, and 45kDa) and several minor (38–19kDa) polypeptides. The set of minor polypeptides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…Herein, we aimed to reveal the link between the dynamics of PTP during capacitation with the AE and the PMI. In our experiment, the incubation for 3 h under capacitating conditions induced the occurrence of capacitation-related events known to occur in bull spermatozoa such as an increase of the BCF [41] (Table 1), and enrichment of the PTP of the sperm head as well as of the flagellum [42] ( Table 2). Furthermore, we confirmed successful capacitation by and increased susceptibility to induced AE by calcium ionophore after 3 h of incubation when compared to non-capacitated control (sample at the beginning of the incubation) [36] (Table 2).…”
Section: Discussionmentioning
confidence: 72%
“…Herein, we aimed to reveal the link between the dynamics of PTP during capacitation with the AE and the PMI. In our experiment, the incubation for 3 h under capacitating conditions induced the occurrence of capacitation-related events known to occur in bull spermatozoa such as an increase of the BCF [41] (Table 1), and enrichment of the PTP of the sperm head as well as of the flagellum [42] ( Table 2). Furthermore, we confirmed successful capacitation by and increased susceptibility to induced AE by calcium ionophore after 3 h of incubation when compared to non-capacitated control (sample at the beginning of the incubation) [36] (Table 2).…”
Section: Discussionmentioning
confidence: 72%
“…The redistribution of lactadherin MFGE8 (aliases p47, SED1) from the apical ridge region of the ejaculated spermatozoa to the entire acrosomal region of capacitated spermatozoa was observed in accordance with previously reported results as well as the presence of two different forms of lactadherin in spermatozoa 34,4447 . Furthermore, MFGE8 can be isolated from OAM-matrix complex of bovine spermatozoa after IVC 45 . We found that the proteasome participates in events linked to the redistribution and degradation of MFGE8, which was hindered by proteasomal inhibitors causing the accumulation of the 48 kDa isoform (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We have observed an identical architect of related proteins in the bovine sperm acrosomal matrix [20,62] reflecting the presence of a similar acrosomal distribution pattern of SP-10 related proteins in nonhuman spermatozoa. Recently, we have shown that proteomic identification of the OMC32 polypeptide (one of the bovine sperm acrosomal proteins), by MALDI-TOF-TOF analysis, yielded 2 peptides that matched the NCBI database sequence of acrosin-binding protein (Bos Taurus; GI: 194666681) [46]. Anti-OMC32 recognized an antigenically related family of polypeptides (OMCrpf polypeptides) in the 38-19kDa range with isoelectric points ranging between 4.0 and 5.1 which are moderately acidic [46].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown that proteomic identification of the OMC32 polypeptide (one of the bovine sperm acrosomal proteins), by MALDI-TOF-TOF analysis, yielded 2 peptides that matched the NCBI database sequence of acrosin-binding protein (Bos Taurus; GI: 194666681) [46]. Anti-OMC32 recognized an antigenically related family of polypeptides (OMCrpf polypeptides) in the 38-19kDa range with isoelectric points ranging between 4.0 and 5.1 which are moderately acidic [46]. Human sperm SP-10 peptides from 24-34kDa have isoelectric points of approximately 4.9; whereas, the isoelectric point 17.5kDa peptide is basic [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation